2006
DOI: 10.1093/njaf/23.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Landowner Satisfaction with Timber Harvesting on West Virginia Forest Stewardship Program Properties

Abstract: We conducted a survey of 3,092 private forest owners enrolled in the West Virginia Forest Stewardship Program to assess program outcomes during its first decade. A component of this assessment was a set of questions designed to bring to light the outcomes of timber harvesting experiences that these landowners may have encountered. Among the 1,672 questionnaires (63% response rate after removing undeliverable addresses) that were returned for our assessment of recommended forestry practices implementation, 445 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Satisfaction with the price received was strongly correlated with overall satisfaction with the harvest. This is consistent with results from McGill et al (2006) who found that West Virginia landowners were 38 times more likely to be satisfied with a timber harvest on their property if they were satisfied with the revenue generated from the sale.…”
Section: Discussionsupporting
confidence: 89%
“…Satisfaction with the price received was strongly correlated with overall satisfaction with the harvest. This is consistent with results from McGill et al (2006) who found that West Virginia landowners were 38 times more likely to be satisfied with a timber harvest on their property if they were satisfied with the revenue generated from the sale.…”
Section: Discussionsupporting
confidence: 89%
“…"Financial returns is the most important reason for timbering" (Koontz 2001, p. 59). In West Virginia, landowner contentment with financial returns generated from a timber harvest has shown to be the most important factor related to their satisfaction level with the transaction (McGill et al 2006). This analysis is concurrent with those findings regarding motivations for timber harvesting activity.…”
Section: Discussionsupporting
confidence: 71%
“…There have been many studies on other relevant groups in the forestry industry such as service foresters, landowners, and the public (Bliss, Nepal, Brooks, & Larsen, 1994;Joshi, Arano, Collins, McGill, & Moss 2007;Manning, Valliere, & Minteer, B, 1996;McGill, Pierskalla, Jennings, & Grushecky, 2006;McGill, Westfall, Gartin, O'Dell, & Boone, 2004;Shindler, List, & Steel, 1993). However, there have not been any studies of forestry or the forestry industry that have included the knowledge and attitudes of high school teachers relevant to the state of West Virginia.…”
Section: Statement Of the Problemmentioning
confidence: 99%